Game-Based Bingo Learning Media in Cultivating Student Self-Confidence in Civic Education (PPKn) Instruction at the Elementary School Level - Inani Nurlaelisah; Mohamad Syarif Sumantri; Linda Zakiah (Universitas Pendidikan Indonesia (UPI), 2023)
This research aims to obtain preliminary information in the development of bingo-based learning media for fifth-grade elementary school students. The bingo game media is designed to provide facilities for civic education (PPKn) learning, aiming to assist students in comprehending PPKn materials and enhancing their self-confidence in the learning process. The development of bingo game media employs the Research and Development (RD) method, and this study is currently in the needs analysis stage. Data collection for needs analysis is conducted through interviews with class teachers and the distribution of questionnaires to students. Based on the research findings, it can be concluded that there are challenges in delivering PPKn materials that involve application, necessitating the use of learning media to boost students' self-confidence in visualizing the materials with the assistance of the bingo game. This conclusion is based on student questionnaire analysis, which indicates that: 1) Students feel confident and actively participate when learning processes involve game-based media. 2) The implementation of learning becomes more enjoyable when utilizing the bingo game.